The Influence of the Work Environment and Compensation on Employee Performance is mediated by the motivation of online drivers in Bekasi City - Kardinah Indrianna Meutia; Hasanuddin, Hasanuddin; Christophorus Indra Wahyu Putra; Wirawan Widjanarko; Gerry Juan Carlos; Rosalina Siagian; Mohamad Sobari (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research tries to analyze the influence of the work environment and compensation on performance mediated by motivation in online motorcycle taxi drivers in Bekasi City. This research was conducted using a quantitative design with 100 respondents from online motorcycle taxi drivers in Bekasi City. The accidental sampling technique with a minimum number of samples using the Lemeshow (1997) approach is an important part of this research. Statistical tools used to test data and draw conclusions from hypotheses using SmartPLS 4.0. The results of this study found that the work environment and compensation had no effect on performance. However, motivation has a direct influence on the performance of online motorcycle taxi drivers. Other findings found that the mediating role of motivation on the influence of the work environment and compensation proved to be influential and strengthened previous findings. This research also focuses on online motorcycle taxi drivers in Bekasi City as a buffer city and a metropolitan city. The theoretical framework and thinking as well as the research instruments in this research are improvements from previous research so that they have their own novelty.